Effect of fuel type on structural and physicochemical properties of solution combustion synthesized CoCr2O4 ceramic pigment nanoparticles. Issue 7 (May 2018) - Chamyani, Samira; Salehirad, Alireza; Oroujzadeh, Nasrin; Fateh, Davod Sadeghi
Abstract: Due to importance and wide applications, CoCr2 O4 ceramic pigment nanoparticles were synthesized via low-temperature solution combustion route by different fuels including ethylenediamine/oxalic acid, ethylenediamine/citric acid, oxalic acid/citric acid and ethylenediamine/oxalic acid/citric acid. Physicochemical properties of the synthesized samples were determined by different techniques such as fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM) and energy dispersive X-ray spectroscopy (EDX) and color/optical properties were evaluated based on CIELAB system by spectrophotometer. Moreover, thermodynamic considerations of combustion reactions for CoCr2 O4 nanopigments formation in terms of calculated adiabatic flame temperature and enthalpy of combustion reaction were studied. The Comparison of results and data showed that cobalt chromite pigment nanoparticles synthesized by using ethylenediamine/citric acid and ethylenediamine/oxalic acid/citric acid fuels exhibited higher purity, smaller crystallite size and lower degree agglomeration.